The PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK SUSU FORMULA SGM: (Survey Pada Konsumen Di Kecamatan Kedungwaringin Kabupaten Bekasi) - Ghita Putri Aprilda; Ratnasari, Ina (Faculty of economcs Universitas Singaperbangsa Karawang, 2021)
The competition in the world of formula milk products makes SGM Formula milk products continue to innovate on their products. The low consumer purchasing decisions are thought to be caused by the price and quality of the product. The purpose of this study was to obtain empirical evidence and to find clarity of phenomena and conclusions about the effect of price and product quality on purchasing decisions for SGM Formula milk products in Kedungwaringin District, Bekasi Regency. This type of quantitative research with the research method used is descriptive verification. The number of research samples was 184 using a simple random technique while data analysis used path analysis. The results showed that the price and product quality partially had a significant effect on purchasing decisions for SGM Formula milk products. Simultaneously, the price and product quality partially have a significant effect on purchasing decisions for SGM Formula milk products. Keywords: price, product quality, purchasing decisions